(untitled) (International Journal of Physiotherapy, 2017)
Background: This study evaluated the effects of an early stretching exercises programme on the range of motion of the shoulder joint and functional recovery in patients with burns. Methods: A randomized controlled study was conducted. Patients from 15 to 55 years of age with a total burn injury surface area (TBSA) of 10% to 45% involving the shoulder joint including axilla were eligible. Participants were randomized into two groups; intervention and a usual care control group, with 110 patients in each group. A standardized protocol was used in the management of intervention group for 14 days. The control group was subjected to usual protocol currently used. The range of Motion (ROM) was measured, and Functional recovery (FR) was assessed with the Quick DASH questionnaire and the Abduction Ladder. Data were obtained before and after the intervention phase and at 3, 6 and 12 months of post-burn period. Results: The mean (SD) age of intervention group and control group were 29.76 [9.81] and 30.31 [9.45] respectively. The mean (SD) TBSA% of intervention group and control group was 26.15[9.45] and 24.60[9.56] respectively. There is a significant beneficial difference (p=<0.0001) in ROM and FR between the intervention group and the control group. Conclusion: This study demonstrated that an early sustained stretching exercise regime significantly improved the ROM and functional recovery of the shoulder joint after a severe burn involving the axilla.